Directive Illocutionary Act: The Command Occurs in The Characters of Jungle Cruise Movie - Putu Devi Maharani; Ni Made Verayanti Utami; Nanda Putri, Ni Luh (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study focuses on finding one kind of directive illocutionary act which is Command that produced by the characters of Jungle Cruise movie and the meaning of the character's utterance in the Jungle Cruise movie. The researcher used theories from Searle and Vanderveken (1985) in order to find out the Commands of Directive illocutionary, Meanwhile, to analyze the meanings of the character's utterance, the writer used the theory that proposed by Halliday and Hasan (1989) regarding the theory context of the situation. This research used a qualitative approach, in which the data was evaluated descriptively using sentences, and a quantitative approach was used to help the understanding of the data by offering a reasonable amount in numerical form. The result of this study, there are 39 data found in the character’s used a command. In this movie there are many commands occurred because this movie tells about the search for a tree of Tears of the Moon, so there are many directions happened from the characters in this Jungle Cruise movie.